EFEKTIVITAS PROGRAM CANTING DALAM UPAYA MENGURANGI ANGKA PERTUMBUHAN STUNTING DI DESA SONGKA KECAMATAN BATU SOPANG - Rio Rianggara; Ferri Wicaksono (Halu Oleo University, 2024)
One dietary issue that needs to be addressed is stunting, particularly in underdeveloped and impoverished nations. A type of growth and development failure known as stunting leads in linear growth abnormalities in toddlers and a build-up of malnutrition that persists from pregnancy until the child is 24 months old. Early on in a child's growth and development, inadequate nourishment can have a fatal effect on the child's mental and physical development. The purpose of this study is to determine how well Songka Village, Batu Sopang District, mother and child health has improved as a result of the stunting control program. Enhancing parental practices via an intervention program to raise nutritional status identification, data collection, and monitoring in order to prevent stunting in 1,000 Hertz. There is a strategy design analysis done based on the prioritized intervention program. The analysis's findings demonstrate that a combination of aggressive tactics, optimizing targeted and sensitive nutritional interventions to promote improvements in the caliber of parenting practices for children under five, is an efficient way to hasten the decline in rural stunting rates. In order to expedite the decline in stunting rates in Songka Village, the long-term strategy makes use of the chance to bolster the government's commitment and the convergence of stunting prevention strategies.